Congress Passes Unambitious User Fee Reauthorization and Expansion: Act Omits Key Provisions Sought by Pharmacy Groups - Barlas, Stephen (MediMedia USA, Inc., 2012)
The FDA’s PDUFA reauthorization bill passes but omits significant safety provisions.